(3cJGH eNJUQ GdYjfs - (3eMeO Hf GdMSf Hf YHjO Gddg Hf ePML GdRHjOj GdCfOdSj GdETHjdj, CHh HcQ , J (B379 (3g` s; (3CHh ehSi,J (B200 (3g` s ((3Ydi Hf eMeO Hf MSf Hf Ydi GdNGfci s)
(3ChdgG (B:s
(3jHOC HCHhGH GdeVGYa s
(3BNQgG (B:s
(3jfJgi HMQa GdjGA s
(3HgG fXGe GdJYbjHIs
(3cJHJ HQSe GdLfGH GdYGdi CejQ MSjfs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3GddZIs